Improving reading skills - Milan Spears, Deanne. (McGraw Hill, 2000)
Improving Reading Skills is designed as a core reader/worktext for introductory and intermediate level developmental reading courses. The selections are of varying lengths and levels of sophistication and represent the types of readings that students will encounter in college and their adult lives. Exercises include short answer as well as multiple choice questions.